1989
DOI: 10.1029/ja094ia12p16987
|View full text |Cite
|
Sign up to set email alerts
|

Observations of neutral circulation at mid‐latitudes during the Equinox Transition Study

Abstract: Measurements of ion drift velocity made by the Millstone Hill incoherent scatter radar have been used to calculate the meridional neutral wind velocity during the Sept. 17-24,1984 period. Strong daytime southward neutral surges were observed during the magnetically disturbed days of September 19 and 23, in contrast to the small daytime winds obtained as expected during the magnetically quiet days. The surge on September 19 was also seen at Arecl'bo. In addition, two approaches have been used to calculate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 42 publications
2
37
0
1
Order By: Relevance
“…Equation (1) uses n O+,O collision frequency, which, as the other ones, is taken from Banks and Kockarts [1973]. However, in some publications devoted to ISR data analyses [Burnside et al, 1987[Burnside et al, , 1988[Burnside et al, , 1991Buonsanto et al, 1989Buonsanto et al, , 1992aBuonsanto et al, , 1992b it was suggested that n O+,O collision frequency should be increased by a factor of 1.7. But later a much lower factor of 1.2-1.4 was recommended by Pesnell et al [1993], Reddy et al [1994], and Davis et al [1995].…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…Equation (1) uses n O+,O collision frequency, which, as the other ones, is taken from Banks and Kockarts [1973]. However, in some publications devoted to ISR data analyses [Burnside et al, 1987[Burnside et al, , 1988[Burnside et al, , 1991Buonsanto et al, 1989Buonsanto et al, , 1992aBuonsanto et al, , 1992b it was suggested that n O+,O collision frequency should be increased by a factor of 1.7. But later a much lower factor of 1.2-1.4 was recommended by Pesnell et al [1993], Reddy et al [1994], and Davis et al [1995].…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…At middle and low latitudes the electric field is usually small, and the height of the ionosphere can be used to infer meridional wind speeds if the electric field is ignored [Miller et al, 1986[Miller et al, , 1987Buonsanto et al, 1989]. Ionosondes typically make hourly soundings and report the peak electron density in the E and F regions, together with the base height of the F region (h'F).…”
Section: Ionosonde Data Analysismentioning
confidence: 99%
“…It should be recalled that all collision frequencies used in our calculations are taken from Banks and Kockarts (1973) and my À y, in particular. But in recent works devoted to the incoherent scatter data analysis (Burnside et al, 1987(Burnside et al, , 1988Buonsanto et al, 1989;Burnside et al, 1991b, a;Buonsanto et al, 1992a, b) it is suggested that this value should be increased by a factor of 1.7. The possible eect of such correction is discussed by Belley et al (1992).…”
Section: Discussionmentioning
confidence: 99%